Current Status Of Global Engineering Education: Mini Review - Ibham Veza; Yusrizal Yusrizal; Muhammad Idris; Nicky Rahmana Putra; Shuaibu Alani Balogun (Fakultas Teknik - Universitas Bung Karno, 2023)
This mini review addresses global engineering education, its diversity, its challenges, and its geographical disparities. Engineering education is essential to sustainable development. The review stresses the need for interdisciplinary engineering that considers social, economic, and environmental concerns. Specialised engineering education packages are increasingly emphasising sustainability. This combination gives engineers the knowledge and abilities to create solutions that meet present needs while preserving resources and future generations. Despite its importance, this brief study highlights global engineering education challenges. Access to high-quality education is unequal, favouring pupils with strong math and science backgrounds. The lack of academic and student diversity may limit perspectives and innovation. Curriculum should also adapt to rapid technological change and industry needs. Internationalising engineering education is complicated by varied standards and teaching methods in different nations, making global comparison and collaboration difficult. The review compares educational systems in India, Malaysia, the US, the UK, China, Australia, Germany, and Indonesia. Regional variances are monitored by certification authorities to ensure compliance with local industry standards. The study emphasises the need for a flexible, well-planned curriculum. Optimal curriculum should align educational goals with industry-specific competencies, be flexible to meet technological developments, and be interdisciplinary. This aims not only meet student educational and career goals but also ensure a workforce with the skills and knowledge to address today's important concerns, particularly sustainability.